A Ilustração luso-brasileira e a circulação dos saberes escravistas caribenhos: a montagem da cafeicultura brasileira em perspectiva comparada Luso-Brazilian Enlightenment and the circulation of Caribbean slavery-related knowledge: the establishment of the Brazilian coffee culture from a comparative perspective - Rafael de Bivar Marquese (História, Ciências, Saúde: Manguinhos, 2009)
A geração dos ilustrados luso-brasileiros encarou a agricultura escravista caribenha como o modelo a ser emulado na América portuguesa. Para tanto, traduziram e publicaram, na virada do século XVIII para o XIX, alguns textos elaborados nas Antilhas. Nesse escopo reformista, a cafeicultura ocupou lugar de destaque. Para compreender o papel desses saberes na montagem da cafeicultura brasileira, comparam-se os casos de Brasil e Cuba. Pretende-se demonstrar que, na colônia espanhola, implantou-se de fato a planta produtiva cafeeira de Santo Domingo, e no Brasil, criou-se uma planta, lastreada em novos padrões de gestão agrícola fundados em saberes locais. The generation of enlightened Luso-Brazilians saw Caribbean slavery agriculture as the model to be emulated in Portuguese America. To do so, at the turn of the eighteenth to the nineteenth centuries, they translated and published some texts originally elaborated in the Antilles. In this reformist environment, the coffee culture occupied a place of prominence. To understand the role of this knowledge in establishing the Brazilian coffee culture, the Brazilian case is compared with the Cuban. The intent is to demonstrate that in the Spanish colony, the productive coffee plan of Santo Domingo was implanted, while in Brazil a plan was created, supported by new standards of agricultural management that were founded on local knowledge.